1999
DOI: 10.1159/000027452
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the Measurement of Corneal Temperature Using a Noncontact Infrared Thermometer

Abstract: Purpose: To assess the variability of corneal temperature and the reproducibility of its measurement by means of a noncontact infrared thermometer in healthy subjects. Methods: The THI-500 noncontact infrared thermometer (Tasco Japan, Osaka, Japan) was used for the measurement of corneal temperature. The reproducibility of corneal temperature measurements was assessed for 5 consecutive temperature readings obtained within 45 min or within 5 days. In addition, the interocular difference in corneal temperature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 14 publications
2
27
0
Order By: Relevance
“…The OPP was calculated as a mean in mm Hg according to the formula: OPP = 2/3 ÂMAP ÀIOP, where MAP (mean arterial pressure) is the diastolic blood pressure plus one third difference between the systolic and the diastolic blood pressure. 2,11,12 Corneal temperature was measured by infrared thermometry (THI-500 noncontact infrared thermometer, Tasco Japan, Osaka) 13 in 1C. Corneal temperature can be used as an estimate of ocular blood flow.…”
Section: Methodsmentioning
confidence: 99%
“…The OPP was calculated as a mean in mm Hg according to the formula: OPP = 2/3 ÂMAP ÀIOP, where MAP (mean arterial pressure) is the diastolic blood pressure plus one third difference between the systolic and the diastolic blood pressure. 2,11,12 Corneal temperature was measured by infrared thermometry (THI-500 noncontact infrared thermometer, Tasco Japan, Osaka) 13 in 1C. Corneal temperature can be used as an estimate of ocular blood flow.…”
Section: Methodsmentioning
confidence: 99%
“…The temperature of the iris and the lens is assumed to be at 37 • C. The temperature at the surface of the cornea is generally considered to lie between 33 and 35 • C [21], and was assumed in this study to be 35 • C. The temperature drop between the iris and the cornea provides the buoyant force mechanism to drive AH in the anterior chamber.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…Besides the temperature increase due to thermal load, the absolute ocular surface temperature at the beginning of the laser treatment will be of interest, as several studies have shown that ocular surface temperature varies over the day, depending for example on the body temperature, e.g. [17][18][19]. The limits of emissivity result in a temperature-spread of 62 K.…”
Section: Case Studymentioning
confidence: 99%